Do firm boundaries matter? The impact of Chinese imports on US conglomerates - Ryoonhee Kim (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2020)
The purpose of this paper is to use China's World Trade Organization accession as a quasi-natural experiment and examine whether conglomeration affects firmss' ability to respond to a significant increase in competitive pressure. Conglomerate segments have higher sales growth and higher profitability than singlesegment firms, when they face intensified import competition. Conglomerates' outperformance is not observed when the markets in which segments operate already have high product market competition. Overall, conglomeration encourages competitiveness, and internal resources are allocated to relatively competitive segments.
Keywords: L22; L25; 330; China's World Trade Organization accession; Conglomerates; Import competition